Kejadian Ikutan Pasca Imunisasi (KIPI) Vaksin Covid-19 Pada Mahasiswa Di Satu Universitas Swasta Indonesia Bagian Barat - Ballsy Cicilia Albertina Pangkey; Dian Riccen Manullang; Maya Rani Simbolon; Ranita Fitriani Naibaho; Masruda A Panjaitan (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2024)
Background: Vaccination is an option used to prevent the spread of COVID-19. Vaccination is a very reliable primary prevention measure against disease. As for the implementation of vaccination activities, it will cause a reaction known as a Post-Immunization Adverse Event (AEFI). Methods: Quantitative method with descriptive analytic design. Sampling using a total sampling technique with a total of 235 student respondents.The research instrument was the AEFI incidence questionnaire. This studywas conducted from February 01 to 28, 2022 with univariate data analysis. Result: The type of vaccine that caused the most AEFI was the Sinovacvaccine. The type of AEFI experienced by most respondents was pain in theinjection area, totaling 100 respondents (92.6%), and the types of AEFI that were not experienced by respondents were fainting and axillary gland enlargement. Implications: The COVID-19 vaccine raises KIPI, the most common ofwhich is pain in the injection area. Pain is one of the local reactions of KIPIthat falls into the mild category and can be immediately resolved with a coldcompress on the painful area. Keywords: COVID-19; AEFI; Vaccines